Workload Analysis of Subdivision Utility Engineering 2 Technicians at PT Konimex Using Full-Time Equivalent - Febrian Naufal Irfansyah; Fakhrina Fahma (Performa: Media Ilmiah Teknik Industri, 2025)
Rapid technological advancement significantly impacts various aspects of life, including company productivity. Company productivity is closely related to human resources. A crucial aspect of human resources in enhancing company productivity is the workload received by employees. PT Konimex is a company planning to implement a new corporate strategy to face Industry 4.0 globalization, which requires evaluating human resources. This study aims to analyze the workload of technicians in the Utility Engineering 2 sub-department at PT Konimex using the Full Time Equivalent (FTE) method and to provide improvement recommendations to optimize workload. Full-time Time Equivalent (FTE) is used to calculate the amount of time required by workers to complete activities within a specific period. To calculate FTE, employee activity and time usage data are required. Therefore, data collection is conducted by compiling the company's historical records and conducting interviews with technicians. After performing calculations, a fishbone diagram is used to analyze the problem and identify alternative solutions. The results show significant variations in FTE values among technicians. Technician Officer A, Technician Level 1 A, and Technician Level 1 B are in an overload condition, Technician Officer B, Technician Level 4 B, and the Head Technician are underloaded. At the same time, Technician Level 1 C and Technician Level 4 A have a normal workload. Improvement recommendations include scheduling preventive maintenance work, optimizing overtime only for critical situations, adhering to work distribution procedures according to SOPs, developing work report input templates, and evaluating preventive maintenance activities